2013
DOI: 10.1111/iep.12008
|View full text |Cite
|
Sign up to set email alerts
|

An improved mouse model that rapidly develops fibrosis in non‐alcoholic steatohepatitis

Abstract: Non-alcoholic steatohepatitis (NASH) is a progressive fibrotic disease, the pathogenesis of which has not been fully elucidated. One of the most common models used in NASH research is a nutritional model where NASH is induced by feeding a diet deficient in both methionine and choline. However, the dietary methionine-/choline-deficient model in mice can cause severe weight loss and liver atrophy, which are not characteristics of NASH seen in human patients. Exclusive, long-term feeding with a high-fat diet (HFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
361
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 380 publications
(422 citation statements)
references
References 44 publications
31
361
1
Order By: Relevance
“…In contrast, this group concluded that Cx32KO mice had increased liver injury and inflammation compared to WT mice. However, the WT mice fed the CDAHFD in that study developed only modest liver injury (ALT, ∼135 IU/L; AST, 49 IU/L; and histologic inflammation scores of ∼2), much lower than reported in multiple published studies showing that a CDAHFD induces severe hepatocellular injury and inflammation, as was the case in our study 24. Thus, it is unclear if the modest injury seen in the control group in their study was adequate to provide the dynamic range for appropriate comparisons between groups.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In contrast, this group concluded that Cx32KO mice had increased liver injury and inflammation compared to WT mice. However, the WT mice fed the CDAHFD in that study developed only modest liver injury (ALT, ∼135 IU/L; AST, 49 IU/L; and histologic inflammation scores of ∼2), much lower than reported in multiple published studies showing that a CDAHFD induces severe hepatocellular injury and inflammation, as was the case in our study 24. Thus, it is unclear if the modest injury seen in the control group in their study was adequate to provide the dynamic range for appropriate comparisons between groups.…”
Section: Discussioncontrasting
confidence: 81%
“…To induce NASH, 6‐8‐week‐old mice were fed a methionine‐and‐choline‐deficient diet (MCDD) for 28 days and then euthanized. Additionally, mice were fed a choline‐deficient, L‐amino acid‐defined, high‐fat diet (CDAHFD) for 9 weeks, at which time they were euthanized 24. Finally, we also used a high‐fat high‐cholesterol diet (HFHCD) for 9 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The CDAHFD model produces rapid and severe lipotoxic hepatic injury by preventing very low‐density lipoprotein production and hepatocyte lipid transport 25. As evidenced by the natural history experiment, the capacity to store lipid is a marker of retained hepatocyte function that dissipates shortly after 6 weeks of diet.…”
Section: Resultsmentioning
confidence: 99%
“…However, this model requires multiple months to develop evidence of hepatic fibrosis, which remains mild to moderate in severity throughout the course of disease. The CDAHFD lacks the metabolic derangements observed in NASH, but the choline deficiency provides a severe lipotoxic hepatic injury and robust fibrotic response 25. We therefore chose to use a choline‐deficiency model despite the acknowledged metabolic limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation